Electrical stimulation induced by a piezo-driven triboelectric nanogenerator and electroactive hydrogel composite, accelerate wound repair. (August 2022) - Sharma, Anjana; Panwar, Vineeta; Mondal, Bidya; Prasher, Dixit; Bera, Milan Kumar; Thomas, Jijo; Kumar, Ajay; Kamboj, Navpreet; Mandal, Dipankar; Ghosh, Deepa
Abstract: Among the numerous types of chronic skin wounds, the treatment of diabetic foot ulcers (DFU) remains a major challenge, in view of its etiology. The high rates of amputation even with the best therapeutic regimens suggest the urgent need for newer approaches. Despite improvement in wound healing with electrical stimulation (ES), it is rarely used in therapy. The advent of wearable devices has renewed interest in this modality of therapy. Whereas such devices focus on ES alone, herein we demonstrate an interactive wound dressing that is capable of providing both ES and an optimal environment for faster healing. The composite dressing containing a conducting hydrogel component constructed with carbonized polydopamine/polydopamine/ polyacrylamide and paired with electroactive electrospun poly(vinylidene fluoride) (PVDF) membrane was capable of generating electrical impulses in response to biomechanical activities. The adhesive and stretchable hydrogel, imparted a moist wound environment apart from protection from bacteria and served as an electrode to direct the electrical impulses generated by the PVDF membrane to the underlying wound due to triboelectrification. The robust mechanical strength of the hydrogel could support physical activities such as walking, stretching etc. The biocompatible dressing encouraged cell growth and migration. The potential of the dressing to improve healing was confirmed in an excisional skin wound model. Evidence of improved re-epithelialization, vascularization and remodeling in wounds covered with the dressing indicated the importance of providing both electrical stimulation and optimal wound environment for faster healing. The proposed approach of using a triboelectric nanogenerator and a conducting hydrogel could aid in the repair of hard-to-heal wounds, such as diabetic foot ulcers. Graphical Abstract: PTENG dressing encourages faster wound healing by providing electrical stimulation and a moist wound environment. ga1 Highlights: Dressing comprises of conductive hydrogel and PTENG nanogenerator. Physical properties of the PTENG dressing are ideal for wound application. Carbonized polydopamine offers conducting property to the hydrogel. Dressing aids healing via electrical stimulation and moist wound environment.